KONSEP PEMASARAN DALAM PERSPEKTIF HUKUM ISLAM - Fathoni, Muhammad Anwar (Jurisdictie: Jurnal Hukum dan Syariah, 2018)
The purpose of this paper is to examine the concept of marketing in the perspective of Islam according to Islamic economic experts. This is a library research with descriptive qualitative approach. The data is in the form of references related to the topic. It is then analyzed qualitatively by data reduction, data presentation, and drawing conclusion. The result shows that the concept of Islamic marketing still depends on the concept of conventional marketing, where Islamic marketing is only used as a marketing tool. Hence, the opportunity to study deeply about the concept of Islamic marketing is still possible to do.